Graves’ Disease Presenting as a Unilateral Breast Mass - Neeka N. Akhavan; Edlira Maska (Case Reports in Medicine)
Introduction. Graves’ disease is an autoimmune thyroid disorder that is the most common cause of hyperthyroidism. Common manifestations of Graves’ disease include weight loss, palpitations, heat intolerance, fatigue, tremors, and exophthalmos, occurring in more than 50% of patients. In rare cases, findings may predominate in one organ system; isolated findings of diarrhea, anxiety, or gynecomastia (as in our case) may occur, distracting from the correct diagnosis. Case Report. We report on a 37-year-old male who presented to the primary care clinic with the chief complaint of a tender right-sided breast mass and with an associated loss of appetite and forty-pound weight loss. Laboratory evaluation revealed suppressed TSH and elevated free T4. A bilateral diagnostic mammogram revealed bilateral gynecomastia. A nuclear medicine thyroid uptake scan was subsequently ordered, which showed the diffusely enlarged thyroid gland with homogenous increased uptake throughout, consistent with Graves’ disease. Conclusion. It is important to keep a high index of suspicion for thyroid disease as hyperthyroid states may be deceiving in presenting with single organ system involvement. Although it is rare, gynecomastia is a known finding in Graves’ disease and can be the presenting sign. Patients with unexplained gynecomastia or breast masses should be screened for thyrotoxicosis.